Warning light - Ricciardi, David (New York Berkley, 2018)
"No one knows what CIA desk jockey Zac Miller is capable of--including himself--when a routine surveillance job becomes a do-or-die mission in the Middle East"--
"Original edition published by the author"--Title page verso.
112521
Keywords: International relations -- Fiction; Americans -- Iran -- Fiction; Spies -- Fiction; Fiction -- Thrillers -- Espionage; Fiction -- Thrillers -- Political; Spy stories; Action and adventure fiction; Spy fiction; Thrillers (Fiction); Political fiction; Suspense fiction